The Epidemiological Pattern and Risk Factor of ESBL (Extended Spectrum Î’-Lactamase) Producing Enterobacteriaceae in Gut Bacterial Flora of Dairy Cows and People Surrounding in Rural Area, Indonesia - Soekoyo, Agusta Reny; Sulistiawati, Sulistiawati; Setyorini, Wahyu; Kuntaman, Kuntaman (Indonesian Journal of Tropical and Infectious Disease, 2020)
Livestock would be a risk factor of resistant bacteria that impact on human health. Rural area with farms as major economic source has become a risk of the spread of the ESBL producing Enterobacteriaceae The aim of the study was to explore the distribution and risk factor of ESBL (extended-spectrum β-lactamase) producing Enterobacteriaceae in the gut bacterial flora of dairy cows and people surrounding farming area. Total of 204 fecal swab samples were collected, 102 from dairy cows and 102 from farmers. Samples were sub-cultured by streaking on MacConkey agar supplemented with 2 mg/L cefotaxime. The growing colonies were confirmed of the ESBL producer by Modified Double Disk Test (M-DDST) and identification of Enterobacteriaceae by biochemical test. ESBL genes were identified by PCR. ESBL producing bacteria were found 13.7% in dairy cows and 34.3% in farmers. ESBL producing Enterobacteriaceae in dairy cows were 6.9% and in farmers of 33.3%. Statistical analysis showed: Distribution of ESBL producing Enterobacteriaceae strain were insignificant among dairy cows and farmers while blaTEM distribution was significantly diï¬€erent (p= 0,035) and use of antibiotic was identified as a risk factor of colonization of ESBL producing Enterobacteriaceae in farmers (p= 0,007). Farmers had suspected as the source of ESBL producing Enterobacteriaceae based on higher prevalence. Further education of appropriate use of antibiotic need to enhance to control risk factor and prevent the colonization of ESBL producing Enterobacteriaceae